Effect of carbon nanofibers on rheological and mechanical properties of cement composites. (29th June 2018) - Wang, Baomin; Fan, Chengcheng
Abstract: Addition of carbon nanofibers (CNFs) in cement composites is an effective method to improve the toughness and crack control capacity. However, the dispersion and influence mechanism of CNFs in cement composites remained some difficulty and controversy. The cement composites mixed with CNFs of good dispersion were well prepared by means of dispersant and ultrasonic treatment. Cement samples with different dosages of CNFs and varying W/C ratios were prepared for testing rheological property and mechanical strength. The results showed that the rheological parameters such as shear stress, viscosity and yield stress increased with the increase of shear rate and dosages of CNFs, while the opposite trend was observed when W/C ratio increased from 0.28 to 0.32. Meanwhile, compared with control sample, the compressive strength and tensile splitting strength of cement composites with 0.1 wt% CNFs increased from 95.2 MPa to 103.8 MPa, and 6.60 MPa to 7.38 MPa, with the increase of 9.0% and 11.8% by W/C of 0.30, respectively. And the microstructure analysis indicated that proper dosage of CNFs could effectively improve the pore structures and interface in cement composites due to nano-core effect, filling effect and bridging effect of CNFs.